Keeping the Ball In Bounds - CARROLL, JOHN (BioCommunications LLC, 2004)
The notion of ‘one drug, many uses’ may drive sales and give hope to sick patients who are willing to try anything. But the government’s crackdown on off-label promotion has biotech companies carefully watching their step, even as CMS policy appears to encourage scientific study of off-label use.